The Influence of Technology in the World of Education - Hutasuhut, Imam Fachrezy; Harahap, Helmi Darwin (Cattleya Darmaya Fortuna, 2024)
This study investigates the influence of technology in the world of education. With the rapid advancement of digital technology, its impact on educational practices and outcomes has become increasingly significant. Through a comprehensive review of existing literature, this research explores the multifaceted influence of technology on various aspects of education, including teaching methods, learning experiences, student engagement, and educational outcomes. The study examines how technology has transformed traditional classroom settings, facilitating the adoption of innovative teaching strategies such as flipped classrooms, blended learning, and personalized instruction. Additionally, it investigates the role of educational technology tools such as learning management systems, interactive whiteboards, and educational apps in enhancing instructional delivery and facilitating student learning. Furthermore, the research explores the broader implications of technology in education, including its potential to democratize access to education, bridge learning gaps, and foster lifelong learning. It also addresses challenges associated with technology integration, such as digital divide, privacy concerns, and the need for teacher professional development. Moreover, the study discusses emerging trends in educational technology, such as the use of artificial intelligence, virtual reality, and gamification, and their potential to revolutionize educational practices and outcomes. By synthesizing empirical evidence and theoretical frameworks, this research provides insights into the transformative power of technology in education and its implications for educational policy and practice. Ultimately, this study contributes to a deeper understanding of the influence of technology in the world of education and highlights the opportunities and challenges associated with its integration into teaching and learning environments. It serves as a foundation for future research and informs evidence-based strategies for leveraging technology to enhance educational outcomes and promote lifelong learning.